Improving students' reading comprehension through predicting strategy instruction: an action research at Cao Ba Quat Upper Secondary school = Nâng cao khả năng đọc hiểu của học sinh thông qua việc giảng dạy chiến lược dự đoán: Nghiên cứu hành động tại trư - Hoàng, Thị Kim Quế (University of Languages and International Studies, 2017)
aThis study aimed at investigating the impact of the predicting strategy instruction on the reading comprehension of 10th grade students at Cao Ba Quat Upper Secondary School and determining the effective techniques to teach predicting strategies to the st (...)